Performa dan Ketahanan Tubuh Broiler dengan Pemberian Tepung Cangkang Kepiting Rajungan (Portunus pelagicus) dan Acidifier Jeruk Nipis (Citrus x aurantiifolia) dalam Pakan : Broiler Performance and Body Resistence after the Addition of Crab (Portunus pelagicus) Shell Flour and Lime (Citrus × aurantiifolia) Acidifier in Feed - soraya faradila; Nuraeni; Febrina Angriani Majid; Andi Ari Maarif (Jurnal Agroekoteknologi dan Agribisnis, 2023)
The main objective of this study was to investigate the impact of adding crab (Portunus pelagicus) shell flour and lime (Citrus ×aurantiifolia) acidifier in broiler feed on their performance and body resistance. The study followed a completely randomized design (CRD) with a total of 80 broiler chickens, divided into 5 treatments with 4 replications. Each replication consisted of 4 broiler chickens. The treatments included: P0 = feed with 19% protein, P1 = feed with 20% protein, P2 = feed with 19% protein + 2% blue swimming crab shell flour, P3 = feed with 19% protein + 1,2% lime acidifier, P4 = feed with 19% protein + 2% blue swimming crab shell flour + 1,2% lime acidifier. The study focused on observing feed consumption, body weight gain, Feed Conversion Ratio (FCR), and lymphoid weight. The results revealed that the addition of crab shell flour and lime acidifier in the broiler feed did not improved performance and body resistance but doesn’t have negative influence.